Exam Ref 70-247 Configuring and Deploying a Private Cloud (MCSE) - Thomas, Orin (Microsoft Press, 2014)
Prepare for Microsoft Exam 70-247-and help demonstrate your real-world mastery configuring and deploying a private cloud using Microsoft System Center 2012 R2. Designed for experienced IT professionals ready to advance their status, Exam Ref focuses on the critical-thinking and decision-making acumen needed for success at the MCSE level. Focus on the expertise measured by these objectives: Design and deploy System Center Configure System Center infrastructure Configure the fabric Configure System Center integration Configure and deploy virtual machines and services This Microsoft Exam Ref : Organizes its coverage by objectives for Exam 70-247 Features strategic, what-if scenarios to challenge you Requires experience with Windows Server, System Center 2012, security, high availability, fault tolerance, and networking in an enterprise environment, and basic skills with SQL Server, Windows PowerShell, and application configuration.